The The Nexus Between Talent Management and Corporate University: Its Impacts on Organizational Performance - Mindarto Totok Oktaruna; Lijan P. Sinambela; Martino Wibowo; Zainur Hidayah (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2023)
Research Aims: This study aims to examine the effect of talent management on organizational performance moderated and mediated by a corporate university. An investigation was performed at Indonesia's Central Finance and Development Supervisory Agency (Badan Pemeriksa Keuangan dan Pembangunan hereinafter abbreviated as BPKP) office. Design/Methodology/Approach: This study used a disproportionate random sampling technique with a total sample of 438 participants representing management. The analysis technique uses a structural equation model using the Smart SEM-PLS application. Research Findings: The results show that talent management significantly affects corporate university and organizational performance. In addition, a corporate university moderates the impact of talent management on organizational performance. Research Limitation & Implications: This research is limited to parties who are considered to represent management at the Financial and Development Supervisory Agency (BPKP), including all structural officials at echelon II level, echelon III/Supervision Coordinator, echelon IV/Sub Coordinator, and intermediate auditors located in 34 Provinces throughout Indonesia.